Visual Hallucinations Associated with Dorsal Thalamic Stroke - Brenes-Salazar, Jorge A. (Journal of Medicine, 2014)
no abstract available DOI: http://dx.doi.org/10.3329/jom.v14i2.19697 J Medicine 2013, 14(2): 226